2017
DOI: 10.1136/bmjopen-2016-012829
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomised controlled multicentre study: the Foraminotomy ACDF Cost-Effectiveness Trial (FACET) in patients with cervical radiculopathy

Abstract: IntroductionCervical radiculopathy due to discogenic or spondylotic stenosis of the neuroforamen can be surgically treated by an anterior discectomy with fusion (ACDF) or a posterior foraminotomy (FOR). Most surgeons prefer ACDF, although there are indications that FOR is as effective as ACDF, has a lower complication rate and is less expensive. A head-to-head comparison of the 2 surgical techniques in a randomised controlled trial has not yet been performed. The study objectives of the Foraminotomy ACDF Cost-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…The overall rate of complications for ACF in our series was low (4.4%), which was comparable with other ACF and PCF series (Table 3) [5,8,[11][12][13]15,16,21,22,24].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The overall rate of complications for ACF in our series was low (4.4%), which was comparable with other ACF and PCF series (Table 3) [5,8,[11][12][13]15,16,21,22,24].…”
Section: Discussionsupporting
confidence: 88%
“…One study that compared ACF and ADR reported similar clinical results but different biomechanical outcomes. Range of motion was preserved for patients who underwent arthroplasty, whereas those who underwent foraminotomies exhibited reduced motion [9,24]. The conclusions of this study were limited by the small number of patients included; thus, a larger series with longer-term outcomes is required to compare ACF with ADR.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To begin with, more studies should focus on the cost-effectiveness of the procedures. Two RCTs 63,64 comparing economic outcomes of ACDF and PCF are already being conducted, but for other comparisons such as CDR versus ACDF, there are no RCTs that focus on patients with pure cervical radiculopathy, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical e cacy is closely related to the e cacy of intraoperative decompression and postoperative intervertebral fusion. [7] To achieve satisfying intervertebral fusion, it is crucial to select a suitable interbody fusion material. The commonly used materials mainly include autologous iliac bone, allogeneic bone, and synthetic materials.…”
Section: Discussionmentioning
confidence: 99%